Total interpretive structural modelling (TISM) of strategic performance management for Indian telecom service providers. Issue 4 (2014) - Neetu Yadav; Sushil
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to develop a total interpretive structural modelling (TSIM) of strategic factors related to performance management in the context of Indian Telecom Service Providers taking dual perspectives in account, i.e. enterprise perspective and subscribers' perspective. Design/methodology/approach – An evolving performance management framework, i.e. flexible strategy game‐card has been taken as the basis to develop the strategic performance management model, where strategic factors have been identified through thematic content analysis and the hierarchical structure of factors has been developed using TISM. Findings – Two total interpretive structural models have been developed, one for enterprise‐related strategic factors, and another for subscriber‐related strategic factors. These hierarchical structures portray the leading and lagging factors of performance, and showcase that financial performance indicators are the lagging indicators. Research limitations/implications – This study has implications for both practitioners and academics. For practitioners, it provides an indicative list of strategic factors relevant for Indian telecom companies, which drive better financial results as well as a list of strategic factors that subscribers consider while assessing the performance of telecom operators. For academics, the methodology used provides a mechanism to conduct an exploratory study by identifying the variables of interest and highlighting their interactions through hierarchical structures. Originality/value – The proposed strategic performance management models developed through qualitative modelling technique is a new effort altogether in the context of Indian telecom operators'. Capturing subscribers' perspective of firm's performance is neglected in existing performance management literature, and this study makes a contribution in this regard.